Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World Proceedings of the ITA-AITES World Tunnel Congress 2023 (WTC 2023), 12-18 May 2023, Athens, Greece - Anagnostou, Georgios; Benardos, Andreas; Marinos, Vassilis P. (Taylor & Francis, 2023)
Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World contains the contributions presented at the ITA-AITES World Tunnel Congress 2023 (Athens, Greece, 12 - 18 May, 2023). Tunnels and underground space are a predominant engineering practice that can provide sustainable, cost-efficient and environmentally friendly solutions to the ever-growing needs of modern societies. This underground expansion in more diverse and challenging infrastructure types or to novel underground uses can foster the changes needed. At the same time, the tunneling and underground space community needs to be better prepared and equipped with knowledge, tools and experience, to deal with the prevailing conditions, to successfully challenge and overcome adversities on this path. The papers in this book aim at contributing to the analysis of challenging conditions, the presentation and dissemination good practices, the introduction of new concepts, new tools and innovative elements that can help engineers and all stakeholders to reach their end goals. Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World covers a wide range of aspects and topics related to the whole chain of the construction and operation of underground structures: Knowledge and Passion to Expand Underground for Sustainability and Resilience Geological, Geotechnical Site Investigation and Ground Characterization Planning and Designing of Tunnels and Underground Structures Mechanised Tunnelling and Microtunnelling Conventional Tunnelling, Drill-and-Blast Applications Tunnelling in Challenging Conditions - Case Histories and Lessons Learned Innovation, Robotics and Automation BIM, Big Data and Machine Learning Applications in Tunnelling Safety, Risk and Operation of Underground Infrastructure, and Contractual Practices, Insurance and Project Management The book is a must-have reference for all professionals and stakeholders involved in tunneling and underground space development projects.